Organizing Data and AI-Supported Tools for Children with Learning Disabilities and Autism - Shakhnoza Khaydarova (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
The rapid advancement of artificial intelligence (AI) has introduced new possibilities for addressing the needs of children with learning disabilities and autism spectrum disorder (ASD). These children require highly individualized educational, therapeutic, and behavioral interventions but often encounter barriers due to fragmented support systems and inefficient data management practices. This article explores how AI-driven tools, when integrated with efficient data organization systems, can transform the care and support provided to children with learning disabilities and autism.